2020
DOI: 10.1111/ggi.14088
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status related to poor health outcomes in older people: Which is better, obese or lean?

Abstract: Good nutritional status is crucial for maintaining growth and health in all stages of life. However, the relationship between nutritional status and health and the effect on various health‐related outcomes differ, depending on the life stage. Many adverse outcomes in older adults, directly linked to different nutritional status, are not present in middle‐aged adults, and their ideal nutritional status may differ. This article will review the optimal nutritional status, mainly evaluated by anthropometric measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 75 publications
(84 reference statements)
0
17
0
2
Order By: Relevance
“…Malnutrition is associated with many adverse events in the aging process of the older [ 7 ], which heavily affect health status and life quality [ 8 ]. Especially in terms of function, it has been proved that malnutrition can lead to functional limitations in the older [ 9 11 ]. This is because nutritional status may trigger changes in the structure and function of muscles.…”
Section: Introductionmentioning
confidence: 99%
“…Malnutrition is associated with many adverse events in the aging process of the older [ 7 ], which heavily affect health status and life quality [ 8 ]. Especially in terms of function, it has been proved that malnutrition can lead to functional limitations in the older [ 9 11 ]. This is because nutritional status may trigger changes in the structure and function of muscles.…”
Section: Introductionmentioning
confidence: 99%
“…Frailty and health risk in older people Dear Editor, Kuzuya 1 reviewed the relationship between nutritional status and health outcomes with special reference to life stage. The author mentioned that there was a shift in medical attention in older adults from metabolic syndrome to frailty.…”
Section: Commentsmentioning
confidence: 99%
“…Changes in total KCL points were 34.5% and 12.1% on 1-year follow-up during the COVID-19 pandemic and non-pandemic period, respectively. In a recent pandemic-related study, including ours, it was indicated that the amount of physical activity was greatly reduced during the COVID-19 pandemic compared with before, [1][2][3][4][5][6] with this inactivity having a huge effect on frailty incidence. In the near future, frail older adults are more likely to need nursing care, 8 and thus more suitable prevention/management strategies for frailty are needed, especially during this pandemic.…”
mentioning
confidence: 99%
“…Ikeda et al showed that the numbers of clinics providing home visits and facilities providing visiting nursing services were positively associated with in-home deaths using 1741 municipalities' data. 2 Furthermore, the number of visiting nurses per population could be associated with that of day service care workers per population. The expenditures of long-term care service except for facility service per user were high among prefectures with both high home death rates and a higher number of visiting nurses per population.…”
Section: Association Between In-home Deaths and Visiting Nurse Servicesmentioning
confidence: 99%